The justice system: constitutional justice in Peru - Roel Alva, Luis Andrés (2022)
What is the role of the Peruvian constitutional justice system in the democratic State? Why is it important? How does it relate with Batman? In this article, the authors analyze the state of the constitutional justice system in Peru and its importance in the protection of human rights and the defense of democracy at the national level. Likewise, from the perspective of art and law, the authors establish a simile between Peruvian constitutional justice and Batman, the dark knight, a famous character from DC Comics who embodies the struggle for just causes.